Push Notification Penghubung Orang Tua dan Guru Berbasis Android Menggunakan Firebase Cloud Messaging - Fransiskus Panca Juniawan; Dwi Yuny Sylfania; David Wijaya (Universitas Bina Darma, 2020)
Information in the form of an agenda made by the teacher is an important thing that parents should know, but the fact is that parents are mostly late in getting all of this information. With the real time features that have been developed in mobile applications today, this problem can be overcome. This study aims to implement the push notification function in applications used by parents and teachers in school. This application is useful as a connector that provides an agenda between users, so all parents can find out the information agenda in real time. We are using prototyping method which consists of the stages of gathering needs, building prototyping, evaluating prototyping, coding, system test, system evaluating, and system implementation. The system built runs well that proved by the blackbox testing carried out. The results of the test show that all the features of the system run intact and well.